Characterization of a Vimentinhigh/Nestinhigh proteome and tissue regenerative secretome generated by human pancreas‐derived mesenchymal stromal cells. (9th January 2020) - Cooper, Tyler T.; Sherman, Stephen E.; Bell, Gillian I.; Ma, Jun; Kuljanin, Miljan; Jose, Shauna E.; Lajoie, Gilles A.; Hess, David A.
Abstract: Multipotent/mesenchymal stromal cells (MSCs) exist within a variety of postnatal tissues; however, global proteomic analyses comparing tissue‐specific MSC are limited. Using human bone marrow (BM)‐derived MSCs as a gold standard, we used label‐free mass spectrometry and functional assays to characterize the proteome, secretome, and corresponding function of human pancreas‐derived MSCs (Panc‐MSCs) with a classical phenotype (CD90+/CD73+/CD105+/CD45−/CD31−). Both MSC subtypes expressed mesenchymal markers vimentin, α‐SMA, and STRO‐1; however, expression of nestin was increased in Panc‐MSCs. Accordingly, these Vimentin high /Nestin high cells were isolated from fresh human pancreatic islet and non‐islet tissues. Next, we identified expression of >60 CD markers shared between Panc‐MSCs and BM‐MSCs, including validated expression of CD14. An additional 19 CD markers were differentially expressed, including reduced pericyte‐marker CD146 expression on Panc‐MSCs. Panc‐MSCs also showed reduced expression of proteins involved in lipid and retinoid metabolism. Accordingly, Panc‐MSCs showed restricted responses to adipogenic stimuli in vitro, although both MSC types demonstrated trilineage differentiation. In contrast, Panc‐MSCs demonstrated accelerated growth kinetics and competency to pro‐neurogenic stimuli in vitro. The secretome of Panc‐MSCs was highly enriched for proteins associated with vascular development, wound healing and chemotaxis. Similar to BM‐MSCs, Panc‐MSCs conditioned media augmented endothelial cell survival, proliferation, and tubule formation in vitro. Importantly, the secretome of both MSC types was capable of stimulating chemotactic infiltration of murine endothelial cells in vivo and reduced hyperglycemia in STZ‐treated mice following intrapancreatic injection. Overall, this study provides foundational knowledge to develop Panc‐MSCs as a unique MSC subtype with functional properties beneficial in regenerative medicine for diabetes and vascular disease. Abstract : Pancreas‐derived mesenchymal stromal cells (Panc‐MSCs) harbor a unique proteome, multipotent potential and tissue regenerative secretome.